Sugarcane Variety Census: Florida 1998 - B. Glaz; Robert A. Gilbert (EDIS, 2003)
This annual variety census of the Florida sugarcane industry for the 1998-99 harvest season is the latest in a long series. Mill managers and independent growers supplied data for 98.1 percent of Florida's sugarcane area. (This estimate was based on information supplied by growers and mill managers, and factoring in that companies that supplied variety information for 8,057 acres last year did not submit information this year.) As a result, the census contains much descriptive and useful information for the Florida sugarcane industry. This document is SS AGR 195, a publication of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published November 2003. Reviewed March 2005.